Impact of maternal neuraxial labor analgesia exposure on offspring's neurodevelopment: A longitudinal prospective cohort study with propensity score matching - Deng, Chun-Mei; Ding, Ting; Liu, Zhi-Hua; He, Shu-Ting; Ma, Jia-Hui; Xu, Ming-Jun; Wang, Lei; Li, Ming; Liang, Wei-Lan; Li, Xue-Ying; Ma, Daqing; Wang, Dong-Xin (Frontiers in Public Health, 2022)
Background: Neuraxial analgesia is widely used to relieve labor pain; its effects on long-term neurodevelopment of offspring remain unclear. This study was designed to investigate the influence of maternal neuraxial labor analgesia on offspring mental development. Methods: This was a predefined secondary analysis of a 2-year prospective longitudinal study. Nulliparous women with single-term cephalic pregnancy preparing for vaginal delivery self-selected neuraxial analgesia or not during labor. Mothers and their offspring were followed up 2 years later. Children’s mental development was assessed with the Bayley Scales of Infant Development. A multivariable logistic model was used to identify factors associated with below-average mental development (Mental Development Index <90). Results: A total of 508 pairs of mothers and children completed a 2-year follow-up. After propensity score matching, 387 pairs were included in the analysis. In both cohorts, the proportions with below-average mental development were slightly lower in children whose mothers received neuraxial labor analgesia, although not statistically significant (in the full cohort: 9.8 % [36/368] vs. 15.7% [22/140], P=0.060; in the matched cohort: 8.3% [21/254] vs. 14.3% [19/133], P=0.065). A higher 2-year depression score (in the full cohort: odds ratio 1.15, 95% CI 1.08-1.22, P<0.001; in the matched cohort: odds ratio 1.09, 95% CI 1.01-1.18, P=0.037), but not neuraxial analgesia exposure, was associated with an increased risk of below-average mental development. Conclusions: Maternal depression at 2 years was associated with the risk of below-average mental development, whereas maternal exposure to neuraxial labor analgesia was not. Clinical Trial Registration: The study was registered with www.chictr.org.cn (ChiCTR-OCH-14004888) and ClinicalTrials.gov (NCT02823418).